IMPLEMENTASI MODEL PjBL DENGAN INFOGRAFIS CANVA UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR IPS PESERTA DIDIK VIIB SMPN 1 KANDEMAN - Wulan Dwi Aryani (Bapelitbang Kabupaten Batang, 2022)
Abstract: This study aims to: 1) implementation of PjBL with infografic canva, 2) improve creativity learning, 3) improve social studies outcomes. This research is an action research using the Kemmis & Taggart spiral design with four stages: planning, implementing, observing and reflecting. The research subjects were 32 class VIIB students. Data collection techniques used were: 1) observation, 2) learning outcomes test, 3) documentation. Data analysis uses comparative descriptive. The results of the study are as follows: 1) Learning PjBL with infografic canva can be implemented in social studies learning, there is an increase in the average of stages of infografic canva from 75,00 (good) to 91,66 (very good) ; 2) There is an increase the average of students creativity from 23,00 (72%), creatif to 27,75 (86,75), very creatif, and 3) There is an increase in the completeness of students' social studies outcomes from 68,75% to 87,50%.